Apomorphine Subcutaneous Injection for the Management of Morning Akinesia in Parkinson's Disease. Issue 1 (25th May 2016) - Isaacson, Stuart; Lew, Mark; Ondo, William; Hubble, Jean; Clinch, Thomas; Pagan, Fernando
Abstract: Background: In patients with motor fluctuations complicating Parkinson's disease (PD), delays in time‐to‐ON with levodopa are common. This open‐label study aimed to assess the effect of apomorphine on time‐to‐ON in PD patients with morning akinesia. Methods: The safety population included 127 enrolled patients, and the full analysis set (FAS) included 88 patients. Patients completed a 7‐day levodopa baseline period recording their time‐to‐ON following each morning dose of levodopa. Patients were titrated to an optimal dose of apomorphine (2–6 mg) while taking trimethobenzamide antiemetic therapy. Apomorphine was injected each morning for a 7‐day treatment period and time‐to‐ON was self‐recorded in 5‐minute blocks. The primary efficacy variable was time‐to‐ON in the apomorphine treatment period versus the baseline levodopa period. Secondary assessments included and global impression scales. Safety and tolerability were assessed through adverse events (AEs). Results: Patients receiving apomorphine achieved mean ± standard deviation (SD) time‐to‐ON 23.72 ± 14.55 minutes, reduced from 60.86 ± 18.11 minutes with levodopa ( P < 0.0001). Dose failures (defined as time‐to‐ON >60 minutes) were more commonly reported with levodopa versus apomorphine (46% vs. 7% of diary entries, respectively). Secondary endpoints supported the primary efficacy findings, with significant improvements from levodopa baseline to apomorphine treatment period (all P < 0.0001). The most common AEs were nausea and dizziness. Most patients who discontinued because of AEs did so in the titration phase. Conclusions: Apomorphine injections significantly reduced time‐to‐ON in PD patients experiencing delayed onset of their morning levodopa dose, and was well tolerated in most patients. After apomorphine treatment, fluctuating patients with morning akinesia experienced rapid and reliable improvement of time‐to‐ON.